Microvascular salvage of a thrombosed total ear replant. Issue 5 (2nd May 2013) - Senchenkov, Alex; Jacobson, Steven R.
<x xml:space="preserve">Abstract</x> Microvascular replantation, when possible, is the treatment of choice for total ear amputations. Both arterial and venous reconstruction should be attempted. The present case report describes a successful total ear replantation in a 45‐year‐old woman whose ear was amputated due to a horse accident. Venous thrombosis subsequently occurred and was managed with anticoagulation and leech therapy. Eighty hours after the replantation, arterial thrombosis took place. The posterior auricular artery thrombosed anastomosis was resected and reconstructed with an interposition vein graft. This report illustrates the feasibility of the successful microvascular salvage of a thrombosed total ear replant. It suggests the need for close clinical monitoring of the replanted ear and prompt microvascular reexploration in an event of the loss of arterial flow. © 2013 Wiley Periodicals, Inc. Microsurgery 33:396–400, 2013.